The Role of Pesantren Culture in Developing Academic Character : A Study on the Positive Impact of the Cultural Environment at Pesantren Luhur Sabilussalam. - M. Ihsan Nashihin; Muhammad Kashif Majeed; Derysmono; Ari Armadi; Agus Syukur (Mimbar Agama Budaya, 2025)
This study aims to investigate the impact and contribution of pesantren culture on the academic achievements of students enrolled in higher education institutions.A pesantren is an institution established by an organization or an individual to provide Islamic education to students (santri) so that they develop strong character and a solid foundation in Islamic knowledge. A pesantren typically consists of four main elements: the kyai (Islamic scholar/leader), santri (students), dormitories, and a mosque.There are four types of pesantren, one of which operates only at night, providing education and religious instruction, while students attend school or university during the day. One example of this model is Pesantren Luhur Sabilussalam. This pesantren offers education, instruction, and guidance exclusively in the evenings, allowing its students to focus on their university studies during the day.This research reveals that pesantren fosters a positive culture that significantly contributes to students' academic character and achievements in higher education. These cultural aspects include the tradition of Islamic study sessions (pengajian), religious activities, the pesantren's overall environment, and positive interactions between students and their teachers (ustadz) and fellow students.These four cultural components within the pesantren have a 45% positive impact on students' academic and non-academic achievements in higher education.This study employs an analytical survey design with a cross-sectional approach and descriptive explanations. Data collection and analysis were conducted using a quantitative approach